Ijtihad dalam Perspektif Ulama Syiah Ithna Ashariyah - Mohammad Baharun (Islamica: Jurnal Studi Keislaman, 2007)
For Sh??ah Ithna Asyar?yah, ijtih?d (intellectual exercise to extrapolate rules from their sources) is an imperative logical practice. Like Sunnism, this school of thought requires that a mujtahid (the one who exercises ijtih?d) has high intellectual qualifications and that tight conditions should be applied to him. To this branch of Shi?ism, a mujtahid has a special place and respected status within its social and religious hierarchy. He represents the missing imam (Imam Mahdi) whom every one in Shi?ism is waiting for his return. With ijtih?d attached to his shoulder, he is considered to be more important as he holds the task of safeguarding and preserving religion.